Designing inclusive community-based geography research experiences across the spectrum of ability. Issue 4 (2nd October 2022) - Atchison, Christopher L.; Hawthorne, Timothy L.; Torres, Hannah R.; Visaggi, Christy C.; Bencivenga, Patricia; Haralson, Joshua; Relyea, Darby; Jarrett, Olga S.
ABSTRACT: Through the voices of both faculty and student authors, we discuss the intentional integration of neurodiversity in an undergraduate, community geography research program. This exploratory case study takes conversations about diversity, equity, and inclusion from theory to practice presenting the development of an inclusive learning community through the lens of education and geoscience education frameworks. Through multiple perspectives advocating for systemic change for inclusive community geography, this paper presents actionable recommendations others in geography can draw from in their own efforts to broaden participation within geography field programs.